2013
DOI: 10.1371/journal.pone.0054641
|View full text |Cite
|
Sign up to set email alerts
|

Brain Processing of Visual Information during Fast Eye Movements Maintains Motor Performance

Abstract: Movement accuracy depends crucially on the ability to detect errors while actions are being performed. When inaccuracies occur repeatedly, both an immediate motor correction and a progressive adaptation of the motor command can unfold. Of all the movements in the motor repertoire of humans, saccadic eye movements are the fastest. Due to the high speed of saccades, and to the impairment of visual perception during saccades, a phenomenon called “saccadic suppression”, it is widely believed that the adaptive mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 49 publications
10
23
1
Order By: Relevance
“…However, we observed that this was not the case and that adaptation occurred equally well. Indeed, we observed that there was equal adaptation across the 3 backward conditions, confirming previous findings (M. Panouillères et al, 2016;Muriel Panouillères et al, 2013). Specifically, it has been shown that intra-saccadic visual feedback received mid-flight during a saccade can also cause saccadic adaptation (Muriel Panouillères et al, 2016;Muriel Panouillères, Gaveau, Socasau, Urquizar, & Pélisson, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, we observed that this was not the case and that adaptation occurred equally well. Indeed, we observed that there was equal adaptation across the 3 backward conditions, confirming previous findings (M. Panouillères et al, 2016;Muriel Panouillères et al, 2013). Specifically, it has been shown that intra-saccadic visual feedback received mid-flight during a saccade can also cause saccadic adaptation (Muriel Panouillères et al, 2016;Muriel Panouillères, Gaveau, Socasau, Urquizar, & Pélisson, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…For example, Bahcall and Kowler (2000) demonstrated backward saccadic adaptation during a task where participants were instructed to saccade partway to a target (75% of the distance from initial fixation point), which could not be based on retinal error. Further, recent evidence has shown that even intra-saccadic visual feedback received mid-flight during a saccade is sufficient to result in saccadic adaptation (Muriel Panouillères et al, 2016;Muriel Panouillères, Gaveau, Socasau, Urquizar, & Pélisson, 2013). These findings support the idea of peripheral visual information being used for adaptation rather than central.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Although intra-saccadic displacement detection is severely impaired (compared to such detection during fixation) due to saccadic suppression of vision (for example, Bridgeman et al, 1975), it has been shown that low frequency motion signals can be detected during saccades (Castet and Masson, 2000). A recent study even suggested that intra-saccadic vision may contribute to saccade adaptation (Panouilleres et al 2013). …”
Section: How Does the Brain Detect Errors?mentioning
confidence: 99%
“…Furthermore, there is a broad gap in our understanding of the relationship between the perceptual detection of error, and that at the service of saccade adaptation. On the one hand, subjects are essentially unable to detect intrasaccadic image displacement (Deubel et al, 1996); on the other, such displacement can cause adaptation (Deubel et al, 1991; Ditterich et al, 1999; Madelain et al, 2013), even when the image is of a point-like target (Panouilleres et al, 2013). What is the difference between perceptual error detection and such detection at the service of adaptation?…”
Section: How Does the Brain Detect Errors?mentioning
confidence: 99%